Attitudes and practices toward stray dog management for rabies prevention among adults in an urban field practice area: a community based cross-sectional study - C. S., Ramalakshmi; Solanki, Mridula J.; K., Vignesh (International Journal of Research in Medical Sciences, 2025)
Background: Rabies is a fatal viral disease predominantly transmitted through dog bites. Although 100% vaccine preventable, India bears a heavy burden causing an estimated 18,000-20,000 deaths annually and accounting for around 36% of global rabies fatalities. Stray dogs remain the primary reservoir, underscoring the urgent need for effective stray-dog and bite-prevention strategies. This study was done to assess the attitudes and practices of adults in an urban field practice area towards stray-dog management for prevention and control of rabies in the community. Methods: This cross-sectional survey in an urban field practice area of a medical college included 380 adults (≥18 years) using convenience sampling across five zones. Over 18 months, investigators used a validated, multi-language questionnaire. Data were analyzed in SPSS 23 with chi-square tests (α=0.05). Results: In this study, 87.1% of the 380 participants reported that stray dogs posed problems in their community, with common concerns including attacks/bites (57.4%), barking/nuisance (22.4%) and environmental spoilage (12.4%). While 71.8% opposed removing and killing stray dogs, 70.3% supported removing them from streets and sheltering them. Just over half (52.4%) endorsed sterilisation and release, and only 9.7% had ever filed a municipal complaint. Additionally, 73.2% believed the government alone is responsible for stray-dog population control. Conclusions: The study found only 38.9% of participants had heard of rabies, with over half of them scoring “poor” on awareness. Despite prevalent stray-dog issues, 73.2% believed only government agencies are responsible. We recommend urgent IEC efforts, proactive dog-population control, community engagement, and a multidisciplinary “one health” approach.